Pembuatan Sistem Informasi Geografis (SIG) untuk Pemetaan Lokasi dan Informasi Data Pembangunan Jalan di Kota Palembang - Muhammad Ramandha Satrya; Wydyanto Wydyanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Road infrastructure development is an important factor in supporting community mobility and equitable regional development. However, road construction data management in Palembang City still faces various problems, such as scattered data, lack of integration, and not yet presented in a map-based visual form. This study aims to implement a Geographic Information System (GIS) as a medium for location mapping and presenting road construction data information in Sematang Borang and Kalidoni Districts, Palembang City. The methods used include field observation, road construction data collection and verification, GPS coordinate point retrieval, spatial and non-spatial data processing, and the development of a GIS system based on interactive digital maps. The results of the study indicate that the system is able to present road construction information in a structured, accurate, and easily accessible manner. This GIS helps improve the efficiency of the monitoring process, data management, and preparation of road construction reports at the Palembang City Public Works and Housing Agency. Thus, the application of GIS can be a supporting solution in decision-making and encourage the digitalization of road infrastructure data management.